The Dynamics of Regional Head Elections in the Digital Era in Indonesia: the Perspective of First-time Voters - Mulyadi, Dedi; Putri, Kayla Andini; Aulia, Salsabila Hadi; Akbar, Rivaldi Aka; Mawardi, Muhamad Fahri; Garnita, Camiliya Fakhriyah (Journal of Legal Studies, 2025)
Indonesia’s Regional Head Elections in 2024 show significant changes in political campaign strategies, especially with the increasing use of social media as the main tool. Social media has become a strategic tool for regional head candidates to convey their vision, mission, and work programs, as well as build their political image. As the dominant platform in the digital era, social media allows for wide, fast, and efficient dissemination of information, especially in reaching young voters who now account for around 60% of the total electorate. Young voters, who are active in using social media, are highly influenced by digital political content from influencers, public figures and peers. The ease of direct interaction between candidates and voters is also an added value that makes social media superior to traditional campaign methods. However, on the other hand, the use of social media in political campaigns faces several challenges, including the spread of disinformation, manipulation of opinions by buzzers and influencers, and potential violations of user data privacy. For this reason, increasing digital literacy and political awareness among the public, especially first-time voters, is important so that voters are more critical in filtering the information received. With the right strategy, social media can be an effective and ethical campaign tool, supporting a healthier and more participatory democracy. This research provides recommendations for candidates and stakeholders to maximize social media responsibly to gain voter support.